MANAJEMEN INOVASI KEPALA SEKOLAH DI ERA INDUSTRI 4.0: OPTIMALISASI TEKNOLOGI DALAM PEMBELAJARAN TK NEGERI PEMBINA BATUMANDI - Chairunnisa; Khuzaini; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
The Industry 4.0 era mandates that school principals manage innovation to optimize learning technology. This study aims to analyze (1) the principal's innovation management strategies, and (2) the enabling and inhibiting factors for technology optimization at TK Negeri Pembina Batumandi. The research utilizes a qualitative approach with a case study design. Data were collected through in-depth interviews with teachers (IG) and school operators (IO), observations, and documentation studies. Data were analyzed thematically. The findings indicate the principal implements a dual strategy: (a) a managerial strategy, focusing on prioritizing the ICT budget and asset management systems (per IO findings), and (b) a transformational/cultural strategy, creating a psychologically safe climate for innovation and employing dialogical supervision (per IG findings). The primary enabling factor is the principal's